Assessment of Lead and Cadmium of Hand Dug Well Around Gold Mining Areas of Rimi Sumaila Local Government Area, Kano State, Nigeria - Abubakar, Musa Yahaya; Dwanga, Danladi Mudwa; Adam, Ansar Bilyamin; Muhammad, Shittu Abubakar; Usman, Usman Sabiu (Darul Yasin Al Sys, 2024)
Heavy metals are essential element that are very important to the soil, their accumulation beyond the permissible limit causes a health risk as it may affect the soil and plants. Mining activities can generate large quantities of heavy metals laden waste which are released in an uncontrolled manner, causing widespread contamination of the ecosystem. Heavy metals are important for normal life psychological process and also provide enormous social and economic benefit to nations, the lung time adverse effect on the environment and public health cannot be overlooked This study investigates the presence of lead and cadmium metals hand dug well around gold mining areas of Rimi Local Government, Kano State. The metals determined were lead and chromium, and the permissible limit for lead in water is 0.1mg/L according to (WHO, 2008). By consideration with the WHO (2008) acceptable limit all the ten-hand dug well water in Rimi are beyond the permissible limit. The highest lead concentrations in water lead to several disease to body organs such as brain, kidney gastrointestinal tracts and central nervous system.